2010
DOI: 10.1007/s11144-010-0173-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of morphology and size on the photocatalytic properties of MoS2

Abstract: The photocatalytic properties of MoS 2 samples including nano-ball, nano-slice and bulk 2H-MoS 2 were evaluated and compared with that of the anatase TiO 2 using the degradation reaction of methyl orange under visible light. The catalytic behaviors of the samples were also characterized using transmission electron microscopy, Brunauer-Emmett-Teller (BET) surface area, ultraviolet-visible spectroscopy, and FTIR spectroscopy. The results show that the bulk MoS 2 and the anatase TiO 2 were almost inactive under v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Polyformaldehyde can decompose on the nano-slices, while it is stable on the nano-balls [21,22]. Methyl orange can remarkably decompose on both nano-balls and nano-slices [26]. It was concluded that LP is easier to decompose on the nano-balls than nano-slices.…”
Section: Xps Characterization Of Wear Scarsmentioning
confidence: 97%
See 2 more Smart Citations
“…Polyformaldehyde can decompose on the nano-slices, while it is stable on the nano-balls [21,22]. Methyl orange can remarkably decompose on both nano-balls and nano-slices [26]. It was concluded that LP is easier to decompose on the nano-balls than nano-slices.…”
Section: Xps Characterization Of Wear Scarsmentioning
confidence: 97%
“…However, the Ref. [26] reported that the MoS 2 nano-balls had an excellent catalytic activity in the degradation of organic chemicals. This indicates that the curved basal surface of the nano-ball is intrinsically different from the normal flat basal surface of the layered 2H-MoS 2 .…”
Section: Xps Characterization Of Wear Scarsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can’t absorb visible light and suffers from fast recombination rate of the photogenerated charge carriers8. In order to overcome these drawbacks, numerous investigations have been devoted to give new types of photocatalysts, where two-dimensional (2D) nanomaterials with exotic electronic properties and high specific surface areas are considered to be the good candidates910, as well as, they have attracted tremendous attention in heterogeneous catalysis111213, sensors14, energy storage1516 and electronics171819.…”
mentioning
confidence: 99%
“…In a previous study, a quick precipitation method was designed to prepare MoS 2 nanoparticles in various shapes [11]. The catalytic properties of the as-prepared nano-MoS 2 were also investigated [12]. TiO 2 has excellent photocatalytic properties for the degradation of unwanted organic compounds in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%